High‐resolution quantitative acoustic microscopy of cutaneous carcinoma and melanoma: Comparison with histology. Issue 5 (1st April 2019) - Youssef, Sarah; Seviaryna, Inna; Shum, David; Maeva, Elena; Malyarenko, Eugene; Rahman, Naila; Maev, Roman Gr.
Abstract: Background: The increased incidence rate of skin cancers during the last decades is alarming. One of the significant difficulties in the histopathology of skin cancers is appearance variability due to the heterogeneity of diseases or tissue preparation and staining process. This study aims to investigate whether the high‐resolution acoustic microscopy has the potential for identifying and quantitatively classifying skin cancers. Material/Methods: Unstained standard formalin‐fixed skin tissue samples were used for ultrasonic examination. The high‐frequency acoustic microscope equipped with the 320 MHz transducer was utilized to visualize skin structure. Fourier transform was performed to calculate the sound speed and attenuation in the tissue. Results: The acoustic images demonstrate good concordance with the traditional histology images. All histological features in the tumour were easily identifiable on acoustic images. Each skin cancer type has its combination of ultrasonic properties significantly different from the healthy skin. Conclusions: High‐resolution acoustic imaging strengthened with quantitative analysis shows a potential to work as an auxiliary imaging modality assisting pathologists to lean to the particular decision in doubtful cases. The method can also assist surgeon to ensure the complete resection of a tumour.